2019
DOI: 10.1038/s41593-018-0295-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological priming causes developmental gene network heterochronicity in autistic subject-derived neurons

Abstract: Autism spectrum disorder (ASD) is thought to emerge during early cortical development. However, the exact developmental stages and associated molecular networks that prime disease propensity are elusive. To profile early neurodevelopmental alterations in ASD with macrocephaly, we monitored patient-derived induced pluripotent stem cells (iPSCs) throughout the recapitulation of cortical development. Our analysis revealed ASD-associated changes in the maturational sequence of early neuron development, involving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
231
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(247 citation statements)
references
References 71 publications
12
231
1
3
Order By: Relevance
“…75,79 This was confirmed in hippocampal neurons in sleepdeprived mice. 78,79 Therefore, increased platelet NAS could echo its levels in the CNS, which in turn supports an abnormal growth acceleration in neural precursor cells from ASD cases as observed in a study by Schafer et al 80 Platelet NAS should be measured in larger ASD cohorts in addition to 5-HT to evaluate its potential as an ASD biomarker.…”
Section: Serotonin Derivatives N-acetyl Serotonin and Melatonin In mentioning
confidence: 76%
“…75,79 This was confirmed in hippocampal neurons in sleepdeprived mice. 78,79 Therefore, increased platelet NAS could echo its levels in the CNS, which in turn supports an abnormal growth acceleration in neural precursor cells from ASD cases as observed in a study by Schafer et al 80 Platelet NAS should be measured in larger ASD cohorts in addition to 5-HT to evaluate its potential as an ASD biomarker.…”
Section: Serotonin Derivatives N-acetyl Serotonin and Melatonin In mentioning
confidence: 76%
“…While this study did not assess any age-related differences between patientand control-derived induced motor neurons, an impressive study by Victor et al [7] demonstrated the importance of modeling old age as a disease-relevant factor in a model consisting of both iPSC-derived and fibroblast-derived medium spiny iNs. As opposed to the most widely believed assumption that the first disease phenotypes emerge in immature neurons, they found heterochronic trajectories in patient cells that were already epigenetically primed for acceleration at the neural stem cell stage [16]. In consistence with the observation that HD iPSC-derived neurons need external stressors to display this disease phenotype, the authors showed that an age-related collapse in proteostasis triggered huntingtin aggregation in an age-and repeat-lengthdependent manner [7].…”
Section: You Are What You Eat: Metabolic Hallmarks Of In Conversionmentioning
confidence: 92%
“…Thus, neuronal subtype specification cannot be easily achieved through the addition of patterning factors such as Wnt or Shh in the media, because the responsive cell type is not present at any time point during conversion. For example, iNs generated from iPSCs through Ngn2-only protocols are predominantly glutamatergic [16,68]. 1B) [25,26,31].…”
Section: Subtype-specific In Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from the SALK institute (CA, USA) did just that, and demonstrated that neurons derived from skin cells of individuals with autism spectrum disorder (ASD) show different patterns of development and growth when compared with cells of neurotypical individuals [3]. …”
Section: Back To the Start; Rewinding Neural Developmentmentioning
confidence: 99%